Evaluation of the Contribution of Construction Professionals in Budgeting for Infrastructure Development in Nigeria - Opawole, Akintayo; Jagboro, Godwin Onajite; Babalola, Olubola; Babatunde, Solomon Olusola (International Journal of Sustainable Construction Engineering and Technology, 2012)
Researchers are of the opinion that the low implementation of public financed infrastructure projects in Nigeria could be correlated to the level of involvement of construction professionals in the budgeting process at macro-level. Though this assertion presently lacks empirical justification, the objective of this study seeks to quantitatively establish this linkage. In order to achieve this, sixteen (16) core budgeting and procurement processes were identified in literature. Furthermore, respondents involved in the study were architects, quantity surveyors, builders, town planners, estate surveyors, engineers (civil, mechanical and electrical), accountants and economists in the public service of Osun State. The fact that infrastructure financing depends majorly on budgetary financing in Osun State provided the justification for choice of the State for the study. Data analysis was through percentage and mean. The study indicates adequate contribution in activities involving post-budgetary process and only progressive trend in pre-budgetary process especially technical and cost evaluation of infrastructure projects and review and approval of budgets for infrastructure projects. Moreover, budgeting process for infrastructure development in Nigeria indicated that majority of projects budgeted for execution lack adequate technical evaluation and cost assessment as a result of inadequate professional involvement. This could be adduced a significant problem of implementation of public financed infrastructure projects in Nigeria. The study provides information on key areas where public policy makers can appropriate construction professionals’ inputs to prepare realistic budget for infrastructure development in developing economy.